Spektrum Tafsir Humanistik Abdurrahman Wahid: Analisis Penafsiran Ayat-ayat Al-Qur’an dalam Wacana Kebangsaan - Wildah Nurul Islami; Abd. Kholid; Nor Syamimi Mohd (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This article examines the humanistic interpretation of the Qur’an by Abdurrahman Wahid in relation to social issues in Indonesia. Utilizing a sociological approach, the article analyzes six spectra of Wahid’s humanistic interpretations that provide solutions to various discourses surrounding these national challenges. First, it addresses the issue of religious exclusivism as presented in Surah Al-Baqarah [2:256], where Wahid emphasizes the necessity of fostering awareness of religious pluralism. Second, in the discourse on education and moral decadence, Wahid advocates for character education through Surah al-‘Aṣr [103:1-3] and Surah al-Shūrā [42:30]. Third, regarding gender discrimination in the social realm, Wahid interprets Surah al-Nisā’ [4:34] and Surah al-Ḥujurāt [49:13], proposing role equality as a solution. Fourth, in the context of state politics, Wahid discusses the challenges posed by the capitalist system, drawing from Surah al-Nisā’ [4:135] and Surah al-Baqarah [2:282], while advocating for leadership oriented towards social welfare. Fifth, concerning the issue of poverty, Wahid references Surah al-Ḥashr [59:7] to emphasize the importance of community empowerment. Lastly, in addressing the cultural crisis, Wahid refers to Surah al-Ḥajj [22:40] to promote awareness of multiculturalism. Overall, this article argues that in the discourse of Qur’anic interpretation, Abdurrahman Wahid has enriched the contextual reading of the Qur’an by employing a humanistic paradigm tailored to the socio-religious and national contexts he faced.